Collaborative project delivery methods: a scoping review - Engebø, Atle; Lædre, Ola; Young, Brendan; Larssen, Per Fridtjof; Lohne, Jardar; Klakegg, Ole Jonny (Journal of Civil Engineering and Management, 2020)
Understanding how to systemise, organise, and finance the design, construction, operation, and maintenance activities are all parameters needed to be optimised simultaneously in a Project Delivery Method. To meet the challenges of increasingly complex projects, a new class of delivery methods is emerging. These methods are often labelled “collaborative” since they seek to align the client’s interest with those of the supply chain. The purpose of this article is to present the current state-of-the-art through a review of 156 identified articles concerning Partnering, Integrated Project Delivery, Alliancing, Relational Contracting, and Relationship-Based Procurement. A framework for the methodological procedure based on the state of the art within qualitative research was elaborated and is reported on in this paper. The results show that there is a range of research on collaborative project delivery methods across the world. By analysing the study purposes, important themes generated and delineated as a) Conceptualisation, b) Implementation and experiences, c) Pros & Cons, d) Building Partnership & Social Dimensions, and e) Performance and Success. The paper provides an overview of collaborative project delivery methods identified in the realm of academic journals. Secondly, knowledge gaps have been identified by creating a summary of the body of evidence.